ALIH KODE DAN CAMPUR KODE DALAM TRANSAKSI ANTARA PENJUAL DAN PEMBELI DI PASAR MODERN TELUK KUANTAN RIAU - Rian Azmul Fauzi; Tressyalina Tressyalina (Universitas Muhammadiyah Surakarta, 2020)
This study aims to describe the forms of code switching and code mixing buying and selling transaction activities in the modern market of Kuantan Bay in the Riau Province, Indonesia. In addition, this research also aims to determine the influence of the events of code switching and code mixing. The basic design of this research is descriptive qualitative. The data are the use of the language by traders and their trading partners in the modern market of Kuantan Bay when making the trading activities. The data are in the form of natural speeches. They were obtained from observations by the researchers from the buying and the selling activities. After the transaction takes place, an in-depth interview with the informant is conducted. Data collection was carried out by listening, recording, taking note, and in-depth interviews. The form of language transfer from the Malay language of Kuantan Singingi into Indonesian is the conclusion of this research. The use of the Kuantan Singingi Malay language is more dominant in the event of code switching and code mixing. The determining factors that influence the code mixing and code switching events are the habits of the speaker, speech partner, the presence of the third speaker, the specific topic and situation of conversation as well as the ability to use language which is motivated by the level of education of both by the seller and the buyer. Keywords: Malay, Code Mixing, Code Switching, Riau